Biofilm models for the food industry: hot spots for plasmid transfer?. Issue 3 (3rd February 2014) - Van, Eva; De, Rosemarie; Van, Els; Devlieghere, Frank; Herman, Lieve; Boon, Nico
Abstract Biofilms represent a substantial problem in the food industry, with food spoilage, equipment failure, and public health aspects to consider. Besides, biofilms may be a hot spot for plasmid transfer, by which antibiotic resistance can be disseminated to potential foodborne pathogens. This study investigated biomass and plasmid transfer in dual‐species (Pseudomonas putida and Escherichia coli) biofilm models relevant to the food industry. Two different configurations (flow‐through and drip‐flow) and two different inoculation procedures (donor–recipient and recipient–donor) were tested. The drip‐flow configuration integrated stainless steel coupons in the setup while the flow‐through configuration included a glass flow cell and silicone tubing. The highest biomass density [10 log (cells cm‐²)] was obtained in the silicone tubing when first the recipient strain was inoculated. High plasmid transfer ratios, up to 1/10 (transconjugants/total bacteria), were found. Depending on the order of inoculation, a difference in transfer efficiency between the biofilm models could be found. The ease by which the multiresistance plasmid was transferred highlights the importance of biofilms in the food industry as hot spots for the acquisition of multiresistance plasmids. This can impede the treatment of foodborne illnesses if pathogens acquire this multiresistance in or from the biofilm.